Does Antenatal Betamethasone Alter White Matter Brain Development in Growth Restricted Fetal Sheep? - Sutherland, Amy E.; Yawno, Tamara; Castillo-Melendez, Margie; Allison, Beth J.; Malhotra, Atul; Polglase, Graeme R.; Cooper, Leo J.; Jenkin, Graham; Miller, Suzanne L. (Frontiers in Cellular Neuroscience, 2020)
Fetal growth restriction (FGR) is a common complication of pregnancy often associated with neurological impairments. Currently there is no treatment for FGR, hence it is likely these babies will be delivered prematurely, thus being exposed to antenatal glucocorticoids. While there is no doubt that antenatal glucocorticoids reduce neonatal mortality and morbidities, their effects on the fetal brain, particularly in FGR babies, are less well recognised. We investigated the effects of both short- and long-term exposure to antenatal betamethasone treatment in both FGR and appropriately grown fetal sheep brains. Surgery was performed on pregnant Border-Leicester Merino crossbred ewes at 105-110 days gestation (term ~150 days) to induce FGR by single umbilical artery ligation or sham surgery. Ewes were then treated with a clinical dose of betamethasone (11.4mg intramuscularly) or saline at 113 and 114 days gestation. Animals were euthanised at 115 days (48 hours following the initial betamethasone administration) or at 125 days (10 days following the initial dose of betamethasone) and fetal brains collected for analysis. FGR fetuses were significantly smaller than controls (115d: 1.68 ± 0.11kg vs 1.99 ± 0.11kg, 125d: 2.70 ± 0.15kg vs 3.31 ± 0.20kg, P<0.001) and betamethasone treatment reduced body weight in both control (115d: 1.64 ± 0.10kg, 125d: 2.53 ± 0.10kg) and FGR fetuses (115d: 1.41 ± 0.10kg, 125d: 2.16 ± 0.17kg, P<0.001). Brain: body weight ratios were significantly increased with FGR (P<0.001) and betamethasone treatment (P=0.002). Within the fetal brain, FGR reduced CNPase-positive myelin staining in the subcortical white matter (SCWM; P=0.01) and corpus collosum (CC; P=0.01), increased GFAP staining in the SCWM (P=0.02) and reduced the number of Olig2 cells in the periventricular white matter (PVWM; P=0.04). Betamethasone treatment significantly increased CNPase staining in the external capsule (EC; P=0.02), reduced GFAP staining in the CC (P=0.03) and increased Olig2 staining in the SCWM (P=0.04). Here we show that FGR has progressive adverse effects on the fetal brain, particularly within the white matter. Betamethasone exacerbated growth restriction in the FGR offspring, but betamethasone did not worsen white matter brain injury.